The use of 18F-FDG PET ratios in the differential diagnosis of common malignant brain tumors - (:unkn) unknown (ELSEVIER SCIENCE INC, 2015)
Objective: This study examined the use of positron emission tomography (PET) ratios to improve the diagnostic ability of 18F-FDG PET/computed tomography (CT) in the differentiation of enhancing brain metastases, central nervous system lymphomas, and gliomas. Materials and methods: Seventy-six patients with malignant brain tumors and available magnetic resonance imaging and PET/CT examinations were included. Results: Among standardized uptake value (SUV)-related parameters tested, tumor maximum SUV to ipsilateral cortex maximum SUV ratio (Tmax:WMimax) and maximum SUV (SUVmax) proved to be the two most valuable parameters for differential diagnosis. Conclusion: in addition to SUVmax,Tmax:WMimax also seems to provide helpful information for the differential diagnosis of lymphomas from other malignant brain tumors. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: 18F-FDG positron emission tomography; Differential diagnosis; Brain metastasis; Glioma; Central nervous system lymphoma; POSITRON-EMISSION-TOMOGRAPHY; NERVOUS-SYSTEM LYMPHOMA; RADIATION NECROSIS; F-18-FDG PET; FDG-PET; C-11-METHIONINE PET; GRADE; RECURRENCE; PERFUSION; GLIOMAS